Tantangan dan Peluang Pengoperasian Kereta Api Cepat dalam Mewujudkan Sistem Transportasi Maju di Indonesia - Safrudin Kurniawan; Galih Satria; Ary Putra Iswanto (Jurnal Syntax Admiration, 2024)
The purpose of this study is to analyze the challenges and opportunities associated with the operation of high-speed trains in Indonesia as part of the transformation towards a more advanced transportation system. This study aims to identify obstacles that may arise in the construction and operation of high-speed railways, as well as look at the economic, social, and environmental opportunities that can result from the adoption of this transportation system. From the results of the analysis of opportunities and challenges, the right strategy will be developed to overcome existing obstacles. This research uses a qualitative approach with descriptive analysis. Data will be collected through literature studies and interviews with resource persons who have met the criteria. Next, data analysis is performed to identify patterns, similarities, and differences in terms of emerging challenges and opportunities. The results of the analysis show that despite facing challenges in infrastructure, regulation, and integration, high-speed rail has great potential in addressing congestion issues, improving connectivity, and bringing positive economic impact. This positive impact also extends to social and environmental aspects, with changes in mobility patterns and the potential for reducing greenhouse gas emissions.